Different approaches for plasma nitrocarburizing of austenitic stainless steel using a plasma-activated solid carbon precursor in a hot-wall reactor - Saeed M. Jafarpour; Anke Dalke; Horst Biermann (Journal of Materials Research and Technology)
This paper highlights the effects of plasma-assisted nitrocarburizing using graphite as an alternative solid carbon precursor in comparison to the state-of-the-art using methane as a gaseous carbon-containing precursor in an industrial-scale hot-wall reactor. In particular, the influence of afterglow and direct glow conditions during short-time nitrocarburizing treatments performed at 440 °C in a N2–H2 plasma on the modifications of the resulting surface properties of AISI 316L austenitic stainless steel is studied comparatively. Therefore, the expanded austenite generated during each treatment is characterized by analysis of the cross-sectional microstructure, surface morphology, phase composition, elemental-depth profile, surface hardness and resistance to dry sliding wear and pitting corrosion. Additionally, the type and concentrations of the treatment-relevant gas species generated during each treatment are measured in real-time using laser absorption spectroscopy. The results revealed the potential of using a plasma-activated solid carbon precursor in a hot-wall reactor for an efficient nitrocarburizing treatment of AISI 316L. In addition, among different investigated PNC treatment conditions, the results of sample treated using plasma-activated graphite bars under afterglow condition provided not only an improved wear behaviour but also an enhanced pitting resistance while the uniform corrosion resistance fairly persevered as compared to the untreated steel.